Trypanosomiasis induced reproductive wastage in West African Dwarf sheep - Akinbamijo, O.O.; Reynolds, L. (International Livestock Centre for Africa, 1993)
This study reports the results of investigations on the effects of Trypanosoma vivax infection in pregnant and lactating West African Dwarf ewes on digestible organic matter intake (DOMI), live weight changes, milk yield pattern, lamb birth weight and growth rate. During pregnancy and lactation, DOMI was lower (P<0.05) in infected ewes. Rate of weight gain did not differ between infected and control animals before 14 weeks post-breeding (eight weeks post-infection). Infected ewes had low maternal weights and poor body condition at parturition, which were associated with low (P<0.01) lamb birth weights and survival. Abortion rate was 15% in the infected ewes with a lamb mortality rate of up to 85%. Lambs born by infected dams had lower weaning weights compared with lambs from control ewes.